PROSPEK EKONOMI SYARIâAH MELALUI PRODUK MUDARABAH DALAM MEMPERKUAT SEKTOR RIIL - Mujibatun, Siti (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2013)
Mudarabah,Â asÂ anÂ iconÂ ofÂ commercialÂ productsÂ inÂ ShariahÂ Economic,Â Â factuallyÂ provenÂ toughnessÂ inÂ facingÂ Â theÂ financialÂ crisisÂ duringÂ thisÂ time.Â ByÂ placingÂ theÂ productÂ mudarabahÂ proportionallyÂ inÂ theÂ financialÂ businessÂ institutionsÂ haveÂ aÂ significantÂ impactÂ onÂ economicÂ sustainabilityÂ inÂ strengtheningÂ theÂ realÂ sector.Â SomeÂ ofÂ theÂ benefitsÂ includeÂ MudarabahÂ product;Â hasÂ Â aÂ rateÂ ofÂ returnÂ higherÂ thanÂ theÂ interestÂ rateÂ applicateÂ onÂ interestÂ bank,Â basedÂ onÂ âproductionâbasedâÂ byÂ Â transactionsÂ basedÂ onÂ realÂ assetsÂ andÂ notÂ solelyÂ onÂ theÂ paperworkÂ thatÂ areÂ derivativesÂ andÂ freeÂ fromÂ elementsÂ ofÂ speculation.Â MudarabahÂ basedÂ onÂ production.Â Therefore,Â theÂ financialÂ crisisÂ canÂ beÂ minimizedÂ becauseÂ theÂ balanceÂ sheetÂ ofÂ companyÂ isÂ stableÂ relatively.Â ToÂ maintainÂ itÂ inÂ theÂ realÂ sector,Â governmentÂ supportÂ inÂ theÂ formÂ ofÂ policiesÂ byÂ strengtheningÂ theÂ roleÂ ofÂ nationalÂ bankingÂ intermediationÂ inÂ theÂ financialÂ andÂ realÂ sectorÂ investmentÂ isÂ neededÂ toÂ minimizeÂ theÂ levelÂ ofÂ unemployment.